Regulação para a estabilidade econômico-financeira ou para o desenvolvimento social: a difícil missão dos Estados nacionais. - Souza, Francisco de Assis Diego Santos de (2016)
This dissertation addresses the issue of regulation and its goals. It is up to national states promoting economic regulation, becoming a dilemma organizing economy to achieve economic and financial stability or to make viable social development goals. In this sense, they were used hypothetical-deductive method of approach and comparative, historical, interpretive and analytical methods of procedure, by techniques of bibliographical and documentary research. The general objective was to question when states may use the financial system for eh benefit of social development. They were presented as specific objectives perceiving the ways of regulation to economic stability, verifying the criteria that governments take into account especially in the context of economic crisis. The hypothesis for the research asks whether, for contributing to the development of states, the financial system would also need to be adjusted for the social and not just for the stability of the own market. Initially, the aim was to show the history of state intervention in the economy and of regulation, the historical and conceptual foreshortening of national and international financial system, until understanding the development expression, proceeding, then, the study of regulation in the financial system, through the existing forms of regulation in the financial sector and discussing about the Basel agreements, as well as deal with issues such as tax collection, fiscal policy and importance of the Central Bank, verifying the need or not of their independence in the context of the relationship between economic and financial stability and/or its contribution to the development of the country, a situation that takes into account social aspects. Finally, the research distinguished the microcredit policy of community banks, the cases of social currency and its legal framework, in addition to solidarity economy, the cooperative banks and public development banks, showing, in this way, ultimately, how would be possible, by financial regulation, achieve social development and the social function of the financial system.